Linguistics as the Science of Language - Maxmudovna, Bozorova Madina (European Journal of Life Safety and Stability (2660-9630), 2022)
Each new foreign language is a whole complex and exciting world that lives and develops according to its own laws. And it is impossible to understand all the beauty of the language, to comprehend its secrets and depths without knowledge of the laws and rules of linguistics. For those who seek to master theories of the internal structure of the English language and are ready to devote their time to self-development and self-improvement, we offer a rich selection of auxiliary literature on the topic of ' linguistics of the English language '. This section is ready to provide a huge amount of useful literature to students studying the theory of linguistics or related courses. Also, teachers of English Linguistics courses will also find a lot of useful information for themselves .Linguistics is the science of natural human language in general and of all languages of the world as its individual representatives. For many centuries, linguistics has been a part of philology - a science that has studied texts, especially ancient ones.